Pendampingan Sertifikasi Halal Kedai Kopi di Kota Tarakan - Anwar, Syaiful; Kartini, Kartini; Irna, Rizky Agusriyanti; Pratiwi, Sulistya Rini (JAST : Jurnal Aplikasi Sains dan Teknologi, 2024)
MSMEs stabilize the Indonesian economy when a global economic downturn hits. In addition, the role of MSMEs is increasing with the community's high interest in consuming MSME products. Information on the packaging is essential to provide information on whether or not the product is suitable for consumption; in addition to the ingredients used, it is also necessary to have a halal label on the product packaging. This community service focuses on coffee shops in Tarakan City that issue halal certificates for processed products. This community service actively involves coffee shop owners who are MSME actors at every stage of the activity and submission. This is because the owners of these MSMEs still do not know the procedures and methods for issuing halal certificates. The results of this service include MSMEs knowing the procedures and provisions for issuing halal certificates and the output of the service in the form of issuing MSME halal certificates.ABSTRAKUMKM merupakan stabilisator dalam perekonomian Indoenesia saat gempuran ekonomi global melanda. Selain itu peranan UMKM semakin besar dengan tingginya minat masyarakat untuk mengkonsumsi produk UMKM. Informasi pada kemasan menjadi penting untuk dapat memberikan informasi layak atau tidaknya mengkonsumsi produk tersebut, selain bahan yang digunakan juga penting adanya label halal pada kemasan produk tersebut. Pengabdian ini berfokus pada Kedai kopi yang ada di Kota Tarakan dalam penerbitan sertfikat halal pada produk olahan. Pengabdian masyarakat ini secara aktif melibatkan pemilik Kedai kopi yang merupakan pelaku UMKM pada setiap tahapan kegiatan dan pengajuannya. Hal ini dikarenakan pemilik UMKM ini masih belum mengetahui prosedur dan cara penerbitan sertifikat halal. Hasil dari pengabdian ini diantaranya UMKM mengetahui prosedur dan ketentuan dari penerbitan sertifikat halal dan output pengabdian berupa terbitnya sertifikat halal UMKM.